GEODEMOGRAPHIC FEATURES OF GEOCRIMINOGENIC SITUATION OF BUKHARA REGION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines some of the reasons and geodemographic features of the geocriminogenic situation in the Bukhara region. Studied the age and gender composition of offenders, the dynamics of crime in various spheres of public life in the regions. Study of Internal Affairs of Uzbekistan Ministry of titles may decrease in crime in recent years, women in the Bukhara region downstream. In particular , 20 1 0 1 6.8 percent of the franchise is set to 9 years, b 201 titles exceeds 1 of 1 percent of the organization to work together. For example,2015-2017 9 , compared with 201 women in a significant reduction in crime ' .